An intervention study through education: The change in attitudes and knowledge of educators about the COVID-19 vaccine - Tuncer, Kevser; Bulut, Irem; Pirincci, Edibe; Ickilli, Nilay (Ios Press, 2023)
BACKGROUND: Reliable and culturally informed health communication is vital in developing positive health behaviors. OBJECTIVE: The aim of this study was to investigate the change in knowledge and attitudes about COVID-19 vaccines by providing training to educators in a province in the east of Turkey. METHODS: A questionnaire developed by the researchers on the basis of the literature was used in this intervention study. It consisted of three parts: socio-demographic information, before education knowledge (BEK) and Attitudes Towards the COVID-19 Vaccine (BEATV), and after education knowledge (AEK) and Attitudes Towards the COVID-19 Vaccine (AEATV). There were 99 teachers, 32 public education teachers, and 144 religious officials who participated in the study. The data were analyzed using SPSS Statistics Pack version 22.0 (IBM, Armonk, NY). Statistical significance value was accepted as p < 0.05. RESULTS: Among the participants, the number of correct answers to all questions increased as a result of the study. There was a positive increase in most of the ATV items after the training. CONCLUSION: Education on COVID-19 vaccines increased awareness as shown by the total number of correct answers and the improved attitude of educators.
Keywords: COVID-19; vaccine; attitude; behavior